BISAP beyond pancreatitis: a new horizon in acute kidney injury prediction - Mark Tawfik; Omar Mourad; Radu Grovu; Chloe Lahoud; Marina Makram; Georges Khattar; Yisroel Grabie; Suzanne El-Sayegh (Journal of Pancreatology)
Background:. Acute kidney injury (AKI) is a common complication in acute pancreatitis (AP), with a significant impact on mortality. The Bedside Index for Severity in Acute Pancreatitis (BISAP) score is well-established for assessing mortality risk in AP, but its utility in predicting AKI is less explored. Methods:. We conducted a retrospective chart review of 779 AP patients across 2 hospitals in New York, USA, from 2016 to 2022. Data on patient demographics, laboratory values, and vital signs were collected. BISAP scores were calculated. The primary outcome was AKI, defined by the KDIGO criteria. Multivariate logistic regression was done to assess the association between the BISAP score and AKI, adjusting for confounders. Secondary outcomes include the association of the BISAP score to hospital length of stay and mortality. Results:. There was a significant association between the BISAP score and AKI, with an odds ratio of 2.36 (95% confidence interval [CI] = 1.42–4.41, P = .001), indicating a more than twofold increase in AKI risk for each point increase in BISAP score. The BISAP score was also significantly correlated with longer hospital stays and increased mortality risk. Conclusion:. The BISAP score is a strong predictor of AKI in AP patients. This association and relation to hospital stay and mortality highlight the potential of the BISAP score as a comprehensive risk assessment tool in AP, especially for early identification of patients at high risk for AKI. This study paves the way for future research into risk-scoring systems for AKI in AP based on significant BISAP components.